Solvability for a class of evolution equations of fractional order with nonlocal conditions on the half-line - Zhanmei Lv; Yanping Gong; Yi Chen (Advances in Difference Equations, 2017)
Abstract In this paper, we get a new form equivalent integral equation for a class of evolution equations of fractional order with nonlocal conditions on the half-line. With the aid of it, the uniqueness of the mild solution is obtained by the Banach contraction theorem. Also, we present the existence and uniqueness theorem of positive mild solutions by the monotone iterative method without assumption of lower and upper solutions.